1980
DOI: 10.1002/ar.1091980103
|View full text |Cite
|
Sign up to set email alerts
|

Lung development and the pulmonary surfactant system: Hormonal influences

Abstract: The effect of hormones on developmental events is not a new area of scientific investigation. However, in the last decade, the developing lung has been the focus of an increasing amount of basic and applied research. Inadequate development of the newborn's respiratory system precludes extra-uterine existence; indeed, such respiratory inadequacy has been a leading cause of death in premature infants. Tremendous strides have been made in understanding the basic cell biology of the developing lung. Much has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 304 publications
(180 reference statements)
0
26
0
Order By: Relevance
“…Extracted samples were dried completely under a stream of air, reconstituted in 1 mL of chloroform and mixed with 9 mL of scintillation fluid. Counts for 3 [H] were obtained as cpm using a Wallac 1409 liquid scintillation counter. Data were expressed as percent surfactant release using the following calculation: [cpm in the extracted media/cpm in the extracted media ϩ cpm in the extracted cells] ϫ 100.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracted samples were dried completely under a stream of air, reconstituted in 1 mL of chloroform and mixed with 9 mL of scintillation fluid. Counts for 3 [H] were obtained as cpm using a Wallac 1409 liquid scintillation counter. Data were expressed as percent surfactant release using the following calculation: [cpm in the extracted media/cpm in the extracted media ϩ cpm in the extracted cells] ϫ 100.…”
Section: Methodsmentioning
confidence: 99%
“…The release of surfactant by ATII cells is a highly coordinated process that is regulated by numerous circulating factors (1)(2)(3). Previous studies have demonstrated that the hormone atrial natriuretic peptide (ANP) is capable of modulating ATII cell function in the adult (4); however, its role in regulating surfactant release in the perinatal period is unknown.…”
mentioning
confidence: 99%
“…GC therapy is widely used in the prenatal and postnatal periods either as a prophylactic or curative measure. Use of prenatal GCs is often motivated by the observed positive effects on lung maturation and surfactant production in preterm babies (1,2), who otherwise stand a high chance of developing respiratory distress syndrome (3) and subsequent chronic lung disease, also known as bronchopulmonary dysplasia (4,5). The positive effects of postnatal GCs on pulmonary inflammatory processes (6,7) and the prophylactic effects against hyperoxic lung injury (8) seem to improve the survival chances of preterm neonates.…”
mentioning
confidence: 99%
“…Although the physiologic importance of this T3 neogenesis remains unclear, it is quite possible that T3 exerts the biologic effects of thyroid hormone and, therefore, is responsible for the morphologic changes in fetal and adult type I1 cells which have been described by a number of investigators (for review, see [20][21][22]. It is also possible that T4, rather than acting as a prohormone, has effects of its own, and that in the course of its activity it is metabolized peripherally to other thyronines such as T3 and rT3 These compounds might then simply represent by-products of thyroid hormone action.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hitchcock and collaborators (20)(21)(22) demonstrated that thyroxine (T4) can accelerate rat lung development and that this acceleration is maximal in the presence of glucocorticoids. Similar findings were noted by Ballard and associates (1, 2) during transplacental stimulation of fetal rabbit lung by an analog of T4 known as DIMIT.…”
mentioning
confidence: 99%